A Novel Nanocomposite Particle of Hydroxyapatite and Silk Fibroin: Biomimetic Synthesis and Its Biocompatibility. (5th August 2010) - Niu, Lin; Zou, Rui; Liu, Qida; Li, Quanli; Chen, Xinmin; Chen, Zhiqing
Abstract : A novel bone-like biomaterial of hydroxyapatite (HAP) and silk fibroin (SF) composite was developed by biomimetic synthesis. The composite was precipitated from drops of Ca( OH ) 2 suspension and H 3 PO 4 solution with SF. With this method, the HAP nanocrystals were obtained by self-assembling on a SF surface whose c-axis was aligned with the long-axis direction of SF in microstructures; this shares the same misconstrues of collagen and HAP with that in the natural bone. The HAP/SF composite then demonstrated that it could promote osteoblast proliferation in vitro and new bone formation in vivo . The novel biomaterial is a promising material for bone replacement and regeneration.